Pengaruh Lama Usaha, Tenaga Kerja Dan Bahan Baku Terhadap Pendapatan Pengrajin Alu Kayu Di Dusun Bangsri - Vera Novitasari; Novita Putri Diantanti; Sutowo Sutowo (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
At present, economic needs in the era of globalization are growing so that the economic sector changes rapidly. Therefore the title of the research in this thesis is "The Influence of Length of Business, Labor and Raw Materials on the Income of Alu Wood Craftsmen in Bangsri Hamlet". The research method used is quantitative research methods. The population used was all wood pestle craftsmen in Bangsri Hamlet with a total sample of 50 respondents and the sampling technique used random sampling. Data collection techniques used questionnaires and assisted by the SPSS Statistics 26 application. The analytical techniques used were: validity test, reliability test, classical assumption test (residual normality test, multicollinearity test, heteroscedasticity test,) and hypothesis testing (T test and F) and multiple linear regression analysis. Based on the results of this study, namely, the length of business, labor and raw materials have no effect and are not significant on the income of wood pestle craftsmen in Bangsri Hamlet. Hamlet. Evidenced by the simultaneous influence of length of business, labor and raw materials significantly on income.